THE CULINARY CRESCENT : A History of Middle Eastern Cuisine - Heine, Peter; Lewis, Peter, 1958- (London, United Kingdom : Gingko Library, 2020)
The Fertile Crescent region has long been regarded as pivotal to the rise of civilisation. Alongside the story of human development, innovation, and progress, there is a culinary tradition of equal richness and importance. The Culinary Crescent shows Heine's deep knowledge of the cookery traditions of the Umayyad, Abbasid, Ottoman, Safavid, and Mughal courts. In addition to a fascinating history, Heine presents more than seventy recipes-from the modest to the extravagant-with dishes ranging from those created by the celebrity chefs of the bygone Mughal era, up to gastronomically complex presentations of modern times. Beautifully produced, and designed for both reading and cooking, The Culinary Crescent is sure to provide a delectable window into the history of food in the Middle East.
Bibliography : pages 229-233.
Translated from the German.
Keywords: Food habits -- Middle East -- History; Cooking, Middle Eastern; Cookbooks